Autism Spectrum Disorders and Gluten/Casein Free Diet Treatment: A Systematic Review (1990-2016) - Çöpür Mazlum; Çöpür Sidar (International Journal of Nutrition, 2017)
Background: High number of patients suffering from autism spectrum disorders utilize dietary intervention methods, especially gluten-free/casein-free diet. In contrast with its’ extensive usage no sufficient and consistent data exist to support its’ efficiency and safety. Objective: The main aim of this systematic review is to provide a general look to the efficiency and safety of gluten-free/casein-free diet treatment for autism spectrum disorders. Method: Studies used in this systematic review are gathered from 3 online databases (PubMed, Embase and the Cochrane Library). Inclusion criteria are established for study selection. Articles published in a peer-reviewed article between 1990 and 2016 in English about our topic of interest and conducted with patients under the age of eighteen (18) are selected and further analyzed (“Level of Evidence” and “Grade of Recommendation” criteria are utilized). Results: Even though some studies with high values of “Level of Evidence” claim that gluten-free/casein-free diet is beneficial for patients suffering from autism spectrum disorders, studies with lower risk of bias demonstrate otherwise. Since studies such as case reports and cohort studies may contain bias associated with small sample size, absence of clear assessment methods, lack of randomization and short treatment period we suggest that there is no sufficient data to support gluten-free/casein-free diet treatment. Conclusion: Due to controversial outcomes from studies that have different “Level of Evidence” we speculate that efficiency of gluten-free/casein-free diet might be related to individual genetic differences. Therefore, studies conducted with large study groups could not provide statistically significant data to support this treatment option. Further studies should be conducted, especially in the field of genetics, in order to test our hypothesis.
Keywords: Gluten free